Harmonization of color measurements in dentistry - Paravina, Rade Dusan; Aleksic, Aleksandar; Tango, Rubens Nisie [UNESP]; Garcia-Beltran, Antonio; Johnston, William Michael; Ghinea, Razvan Ionut (Elsevier B.V., 2021)
Natural teeth and tooth-colored dental materials are translucent and encompass a relatively narrow color range. Calibration of color measuring instruments using opaque ceramic tiles arises the question of suitability for dental application. The purpose of the study was to evaluate the effects of harmonization of color measurements among instruments with the same optical geometry (spectrophotometer - diffuse/8 degrees or spectroradiometer -45 degrees/0 degrees). The newly proposed method aimed to create a standardized protocol and quality control tool for color measurements in dentistry using sets of standardized dental material specimens of different color and translucency. A total of 41 specimens were measured at a coordinating center (CC) and three research sites (RS). Total color differences between CC and RS exhibited significant reduction upon implementation of correction factors. The proposed harmonization using tooth-colored translucent materials proved to be valid.
Keywords: Color harmonization; Dentistry; Measuring instrument; Psychophysics; Tooth-colored dental materials; Color tolerance